Factors Impact of the Stock Market Performance During the Covid-19 Crisis - Thomas Sumarsan Goh; Henry Henry; Erika Erika (Faculty of Economic and Business, 2024)
Research originality: This research adds the exchange rate variable and the use of the Vector Autoregressive (VAR) model that can add to the financial literature.Research Objectives: This study examines how macroeconomics can impact a business during a crisis. The stock market has associated access with new COVID-19 cases and new deaths in Indonesia. During the pandemic, the exchange rate is critical, so this study observes the exchange rate of IDR against USD. This paper investigates the relationship between new cases, new deaths, and the exchange rate with the stock market index.Research Methods: The study retrieves the daily data from March 2, 2020, to June 30, 2022, from Our World in Data, Indonesia's stock exchange, and Indonesia's Statistic Central Bureau. We have used the ADF, Vector Autoregressive (VAR) Model, impulse response function, and the Toda Yamamoto causality test. Empirical Results: The findings reveal a significant negative impact of new COVID-19 cases, new deaths, and exchange rates on the stock market. Toda Yamamoto's causality analysis reveals substantial evidence of unidirectional daily growth of new COVID-19 deaths in the stock market and a bidirectional causality of new COVID-19 cases and new COVID-19 deaths.Implications: The policy implications of this study are to stabilize markets, impact overall financial stability, support entrepreneurship, and develop a competitive market environment that can encourage innovation. JEL Classification: C5, E31, F31How to Cite:Goh, T. S., Henry, H., & Erika, E. (2024). Factors Impact of the Stock Market Performance During the Covid-19 Crisis. Etikonomi, 23(1), 47 – 62. https://doi.org/10.15408/etk.v23i1.32005